PROFIL PEMAHAMAN KONSEP SISWA KELAS VIII G SMP NEGERI 3 PALU PADA MATERI STATISTIKA DITINJAU DARI JENIS KELAMIN: Conceptual Understanding Profile of Class VIII G Students at SMP Negeri 3 Palu in Statistics Subject Based on Gender - Ananda, Rini; Sugita, Gandung; Anggraini; Alfisyahra (Universitas Tadulako, 2024)
This research aims to obtain a description or portrayal of the conceptual understanding of 8th-grade students in class G at SMP Negeri 3 Palu in solving statistics problems, with a focus on gender differences. This study adopts a descriptive research design with a qualitative approach. The research subjects are 8th-grade students in class G at SMP Negeri 3 Palu. Data were collected through written tests and interviews. The results of this research indicate that male students have a better conceptual understanding compared to female students based on conceptual understanding indicators. Male students can fulfill four out of five indicators, while female students fulfill three out of five conceptual understanding indicators. Both male and female students can articulate the concepts of mean, median, and mode in their own words. They can present data in table form with the correct arrangement. Male and female students can solve mean problems using appropriate algorithms. Male students can classify modes, whereas female students struggle to classify modes accurately. Both male and female students find it challenging to associate the concept of median with the concept of mean.